SOME COMMENTS ON RETROSPECTIVE PLOT (Scientific journal of the Fergana State University, 2023)
The article analyzes the theoretical views of Russian and Uzbek literary critics on the terms "retrospective plot", "functions of the retrospective plot", their types, features, application in fiction.